Stereoscopic Near-Infrared Fluorescence Imaging: A Proof of Concept Toward Real-Time Depth Perception in Surgical Robotics - Munford, Maxwell J.; Rodriguez y Baena, Ferdinando; Bowyer, Stuart (Frontiers in Robotics and AI, 2019)
The increasing use of surgical robotics has provoked the necessity for new medical imaging methods. Many assistive surgical robotic systems influence the surgeon's movements based on a model of constraints and boundaries driven by anatomy. This study aims to demonstrate that Near-Infrared Fluorescence (NIRF) imaging could be applied in surgical applications to provide subsurface mapping of capillaries beneath soft tissue as a method for imaging active constraints. The manufacture of a system for imaging in the near-infrared wavelength range is presented, followed by a description of computational methods for stereo-post-processing and data acquisition and testing used to demonstrate that the proposed methods are viable. The results demonstrate that it is possible to use NIRF for the imaging of a capillary submersed up to 11 mm below a soft tissue phantom, over a range of angles from 0o through 45o. Phantom depth has been measured to an accuracy of ±3 mm and phantom angle to a constant accuracy of ±1.6o. These findings suggest that NIRF could be used for the next generation of medical imaging in surgical robotics and provide a basis for future research into real-time depth perception in the mapping of active constraints.